Assessment of response of microdermabrasion with 2% kojic acid in melasma - Gupta, Kalpana; Agarwal, Nidheesh (International Journal of Research in Medical Sciences, 2017)
Background: Melasma is an acquired disorder of hypermelanosis and several therapeutic modalities is in use to treat melasma. Kojic acid is a popular depigmenting agent, but its hydrophilic nature limits its transepidermal penetration. Microdermabrasion has been reported to increase the penetration of topical preparations. The objective of the study was to compare the efficacy of daily kojic acid (2%) gel along with biweekly microdermabrasion versus daily kojic acid (2%) gel alone in Indian patients. Methods: This study was carried out in 60 patients with melasma which were randomised into 2 groups of 30 patients each. The group I patients were treated with kojic acid 2% gel along with biweekly microdermabrasion, and group II patients were treated with kojic acid 2% gel alone. The results were assessed and compared after 12 weeks. Results: Both objective assessment and subjective assessment did not reveal a statistically significant difference in the treatment efficacy of two groups. However, the patients who received biweekly microdermabrasion were significantly more satisfied than those who did not. Conclusions: Microdermabrasion does not appear to have any synergistic effect with kojic acid in decreasing pigmentation in melasma. However, it does have a placebo effect on the patient.